Trimodal grain structure enables high-strength CNT/Al-Cu-Mg composites higher ductility by powder assembly & alloying. Issue 1 (2nd January 2021) - Fu, Xiaowen; Tan, Zhanqiu; Min, Xinrui; Li, Zan; Yue, Zhenming; Fan, Genlian; Xiong, Ding-Bang; Li, Zhiqiang
Abstract : A grain structure tailoring strategy was implemented by powder assembly & alloying in carbon nanotube reinforced Al-Cu-Mg composites. Tensile tests revealed that composites with trimodal grain structure had an outstanding combination of strength and ductility, surpassing that of composites with simpler grain structures (e.g. bimodal and unimodal structure). An in-situ tracking of the strain distributions and computational simulations were jointly employed to provide insight into the underlying mechanisms. The results unravel that the trimodal grain structure is more prone to facilitate strain hardening and alleviate strain/stress concentrations, thereby rendering the composites high yield strength and large tensile ductility. IMPACT STATEMENT A novel trimodal grain structure was designed for the first time to achieve an excellent strength-ductility combination in CNT/Al-Cu-Mg composites. GRAPHICAL ABSTRACT: UF0001